Crosstalk noise minimization in novel through silicon via structures - Nageswara Rao, K; Veerendra Nath, G; Hari Kishore, K (International Journal of Engineering and Technology, 2018)
In recent trends, through silicon via (TSV) is essential Technologies for 3-D IC integration because of its short interconnects length and high interconnect density. Beyond the existing structure of TSV, this paper provides a novel structure to investigate the crosstalk effect and same is simulated by using a SPICE simulator and 3-D field solver. The structure of the TSV comprises of copper surrounding by insulating liner, and silicon substrate. In existing structures, silicon dioxide (Sio2) is used as insulating liner because of its material compatibility with silicon substrate. Several researches provide the problem of using Sio2 is due to its high dielectric constant; as a consequence delay will increase. Therefore, Sio2 is not appropriate for high performance applications. In this work, a novel TSV structure is reported to improve the TSV performance which uses poly-propylene polymer liner instead of oxide liner. Signal TSV is enclosed by using a poly-propylene liner and amid the analysis with doping region is created around the ground TSV. For comparison purposes, conventional and proposed TSV structures are simulated. The proposed TSV’s structure simulation results in 30% decrease in crosstalk over existing TSV structures.